VITAMIN D RECEPTOR GENE POLYMORPHISMS AND HAPLOTYPE ANALYSIS IN TYPE 2 DIABETES MELLITUS PATIENTS FROM NORTH INDIA - Taneja, Nancy; Khadgawat, Rajesh; Mani, Shalini (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â Â Objective: Vitamin D receptor (VDR) mediated Vitamin D signaling is important for expression of insulin gene and glucose transporters, which help in glucose uptake by cells. Current evidence suggests that four common polymorphisms (FokI, BsmI, ApaI, TaqI) of VDR gene are associated with Type 2 diabetes mellitus (T2DM) in different populations. However, there is a scarcity of data on VDR polymorphisms from Indian population. Methods: In the current study, total genomic DNA was isolated from 100 well-characterized T2DM patients and 100 healthy controls. We investigated the prevalence of FokI and ApaI polymorphisms in VDR gene of these patients by polymerase chain reaction-restriction fragment length polymorphism-based method. Taking help of our previous published data on TaqI and BsmI polymorphisms in same patients, the haplotype study was also conducted. Statistical analysis of data was performed using SPSS 21.0 software. Haplotype and linkage disequilibrium analysis was performed by Haploview software. Results: Both the wild (TT) and mutant (CC) genotype of FokI polymorphism showed a significant difference between patients and controls (p<0.001 and p<0.001, respectively). The frequency of mutant allele (C) was also significantly higher in T2DM patients than the controls (p<0.001). In case of ApaI, frequency of wild (GG) and mutant (CC) genotype was significantly different in patients and controls (p=0.017 and p=0.034). As per haplotype analysis, the CACT haplotype was predicted to be of significance in patients and consists of mutant alleles of three polymorphisms (FokI, BsmI, ApaI). Conclusion: Our study supports the association of FokI and ApaI polymorphism in T2DM. The haplotype analysis also indicates that the combinations of mutant allele of different VDR polymorphisms are probably responsible for increased susceptibility of these individuals toward T2DM.